ACID-INDOL-3-BUTTIRY AND COLLECTION TIME INFLUENCING ON THE ROTATION OF Odontonema strictum (Nees) O. Kuntze - Mendonça, L. P.; Batista, J. N.; Magalhães, W. B.; Ferreira, J. P.; Bucher, C. A. (Revista Brasileira de Engenharia de Biossistemas, 2018)
Odontonema strictum (Nees), which originates in Central America, belongs to the Acanthaceae family and is important in its use as an ornamental plant. Therefore, knowledge about its propagation by cutting is necessary. However, technical information regarding the vegetative responses of the species to the use of phytoregulars and collection seasons is incipient. The objective of this work was to evaluate the effect of indole-3-butyric acid (AIB) and the collection time on the rooting of cuttings of Odontonema strictum (Nees) O. Kuntze. For this, herbaceous, semi-hardwood and woody stakes were treated or not (control) with IBA at concentrations of 1000 and 2000 mg.L-1. After the treatment, the cuttings were buried in coarse sand. The experiment was carried out in two distinct seasons (summer/fall and winter/spring). The evaluated characteristics were percentage of rooted cuttings, survival of cuttings, number of shoots per cutting, length of the largest shoot and length of the largest root. The results show that the species has great regenerative capacity and can be considered as easy rooting, independent of the application of the phytogulator (AIB) and the type of cutting used. The summer/autumn season proved to be more suitable for collecting cuttings, but the species presents no difficulty in being propagated throughout the year.